Recent advances in gold nanostructure-based biosensors in detecting diabetes biomarkers - Jamshidnejad-Tosaramandani, Tahereh; Kashanian, Soheila; Omidfar, Kobra; Schiöth, Helgi B. (Frontiers in Bioengineering and Biotechnology, 2024)
1. Au-NSs presented outstanding properties such as chemical stability, high electrical conductivity, a large specific surface area, low cost of synthesis, ease of functionalization.2. The utilization of Au-NSs in biosensors is an excellent opportunity in detecting all diabetes biomarkers such as glucose, HbA1c, GA insulin, IAA, and GADA.3. Au-NSs can improve the efficiency, sensitivity, specificity, and stability of the diabetes biosensors.4. The Au-NSs properties can increase the efficiency, sensitivity and specificity of the biosensor through intrinsic specific molecule recognition capacity, signal transduction amplification in different methods, fast electron transferring, the ability to stabilization of structures of GOx and/or antibodies over proper immobilization on electrodes, serving as fluorescent and colorimetric materials.5. Further consideration is required to translate Au-NSs-based technologies into routine and functional biosensors, as the properties of Au-NSs are dependent to their size, shape and spatial arrangement.